the Influence of Marketing Communication on Customer Loyalty at PT. Image Express Delivery Van (TIKI) Sumedang Branch : pemasaran - ginanjar, yayat; Dewi, Kisthi Hanila; Sutisna, Nana (Jurnal Ekuisci, 2024)
Abstract. Marketing communications can be an effective form of communication channel to handle consumer complaints effectively and efficiently. By paying attention to the importance of marketing communications, companies can design more effective communication strategies to achieve their marketing goals, and can build strong customer loyalty. In this research, the method used is a quantitative method. According to Priyono (Sahir, 2021:13) "Quantitative research methods are scientific thinking in which there is a process of idea formation and ideas are implemented strictly using nomothetic principles and using deductive patterns." Marketing Communications (X) has a positive and significant influence on Customer Loyalty (Y) at PT. Citra Van Titipan Kilat (TIKI) Sumedang Branch with a total influence of 51.1% while 48.9% is the influence of other variables not examined in this research. Then, based on the t test, the calculated t is 9.679 and the degrees of freedom (nk-1) or 100-1-1 98 are obtained for the t table of 1.985 so that the calculated t > t table (9.679 > 1.985). This means that H0 is rejected and H1 is accepted, so there is a positive and significant influence.